2009
DOI: 10.1111/j.1365-2893.2009.01141.x
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus infection is a risk factor for gallstone disease: a prospective hospital‐based study of patients with chronic viral C hepatitis

Abstract: We evaluated the prevalence and the risk factors for gallstone disease in patients with chronic hepatitis C infection. We investigated 453 consecutively admitted patients with chronic infection with hepatitis C virus (HCV) (cirrhosis excluded) and 879 patients without liver disease (October 2006-April 2007). Gallstone disease was diagnosed if gallstones were present at ultrasonography or if there had been a previous cholecystectomy. Variables evaluated were age, gender, gallstone heredity, body mass index, wai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 37 publications
(46 reference statements)
2
36
2
Order By: Relevance
“…A US cohort comprising of 13,465 people from the National Health and Nutrition Examination Survey (NHANES) III cohort found an increased risk of gallstones (OR 3.2, 95% CI 1.08–9.45) and cholecystectomy (OR 4.57, 95% CI 1.57–13.27) in men with HCV compared to HCV-negative men [113]. The above association was not reported in women in this study, however the increased risk of gallstones in both genders with HCV has been supported by others [114,115]. In HCV patients, Acalovschi et al [114] reports central obesity and liver steatosis as significant risk factors both of which have been linked to insulin resistance [116,117].…”
Section: Environmental Factorscontrasting
confidence: 43%
See 1 more Smart Citation
“…A US cohort comprising of 13,465 people from the National Health and Nutrition Examination Survey (NHANES) III cohort found an increased risk of gallstones (OR 3.2, 95% CI 1.08–9.45) and cholecystectomy (OR 4.57, 95% CI 1.57–13.27) in men with HCV compared to HCV-negative men [113]. The above association was not reported in women in this study, however the increased risk of gallstones in both genders with HCV has been supported by others [114,115]. In HCV patients, Acalovschi et al [114] reports central obesity and liver steatosis as significant risk factors both of which have been linked to insulin resistance [116,117].…”
Section: Environmental Factorscontrasting
confidence: 43%
“…In HCV patients, Acalovschi et al [114] reports central obesity and liver steatosis as significant risk factors both of which have been linked to insulin resistance [116,117]. In cholesterol gallstones as well as in chronic HCV infection, insulin resistance is suggested as being their causal link given its ability to increase bile cholesterol saturation [114]. …”
Section: Environmental Factorsmentioning
confidence: 99%
“…Previous studies have reported conflicting results for chronic hepatitis B infection as a risk factor for cholelithiasis, [21,22] and previous reports suggested chronic hepatitis C as a risk factor for cholelithiasis. [23] Chronic liver inflammation increases the risk of cholelithiasis [24] and chronic inflammation caused by chronic hepatitis B or C might increase the risk of cholelithiasis. Risk of cholelithiasis was reported to show correlation with the degree of liver cirrhosis.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Western studies shows that the contributing risk factors associated with gallstones are ethnicity, genetics, gender (F > M), age,obesity, fertility, metabolic diseases, hepatitis C, cirrhosis, and high caloric intake. [7][8][9][10] The relationship between blood cholesterol, LDL, and HDL levels and cholesterol gallstone formation is complex and multifarious.…”
Section: Introductionmentioning
confidence: 99%